PENINGKATAN LITERASI PENCEMARAN PADA EKOSISTEM PESISIR PADA SISWA KELAS XI SMA NEGERI 7 AMBON - Sophia Fendjalang; Krisye Pasanea; Endang Jamal; Ruku R Borut (Universitas Mataram, 2026)
The dynamics of urban development and coastal community activities have precipitated a progressive escalation of environmental pressures, manifested through aquatic pollution originating from the direct discharge of domestic and industrial effluents into water bodies, solid waste accumulation, riverine runoff, and the increasing volume of plastic waste alongside heavy metal contaminants such as mercury and lead. Environmental literacy among senior high school students plays a significant role in shaping conceptual understanding, attitudes, and behavioral responses toward pollution-related issues, particularly in coastal regions. Community Service Activities (PKM) grounded in environmental education constitute one of the strategic approaches for enhancing students' comprehension of coastal ecosystem pollution literacy, especially among eleventh-grade students of SMA Negeri 7, who are at a critical stage of cognitive development in constructing ecological awareness. The PKM activity was conducted on Friday, March 6, 2026, from 08:00 WIT until completion, held in the teachers' meeting room of SMA Negeri 7, Ambon. The target participants of this PKM activity were eleventh-grade students, totaling 60 individuals. The activity comprised three sequential phases, commencing with preparation, followed by implementation, and concluding with activity evaluation. The findings of this activity indicate that the environmental literacy of students at SMA Negeri 7 Ambon demonstrated notable improvement regarding coastal ecosystem pollution, accompanied by a heightened awareness to preserve and conserve the environment, as evidenced by their active engagement in discussions and satisfactory post-test outcomes. Furthermore, this activity fostered productive synergy between higher education institutions and senior high schools in cultivating students' intellectual capacities, who represent the future generation of the nation.